The cheerleaders of doom - Buckley, Michael, 1969- (Buckley, Michael, 1969- NERDS (New York, N.Y.), 2011)
When a former member of NERDS turns into a villainous cheerleader, Matilda "Wheezer" Choi and the rest of the NERDS must infiltrate the cheerleader squad and save the world from a machine that wreaks havoc by entering other dimensions.